Climate change and news audiences report 2024: analysis of news use and attitudes in eight countries - Ejaz, W; Mukherjee, M; Fletcher, R (Reuters Institute for the Study of Journalism, 2025)
This third annual report examines how people across eight countries engage with climate change news and information, offering fresh insights from 2024 data while highlighting trends from 2022 and 2023. It explores media use patterns, trust in sources, exposure to misinformation, and perceptions of extreme weather events. Despite escalating climate risks, public attitudes display “climate perception inertia”, with limited shifts over time. Television and online platforms remain the dominant sources of climate news, and scientists continue to be the most trusted figures. The report also analyses perceptions of global initiatives like COP29 and their influence on public understanding. By connecting three years of data, it underscores the critical role of media in shaping engagement and identifies opportunities for more effective communication. These findings offer valuable insights into evolving public attitudes and the media’s role in addressing the climate crisis.